1972
DOI: 10.1159/000180170
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of the Normal Human Kidney Following Contralateral Nephrectomy

Abstract: Intravenous pyelograms were performed on 22 kidney donors, both before and from 2 weeks to 4 years after nephrectomy. A significant increase in kidney size was demonstrated by four different measurements. There was no significant difference in the increase in kidney size between the donors over 40 and those under 40 years of age. A significant increase in glomerular filtration rate per kidney was also found, but this increase could not be correlated with the increase in kidney size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
2

Year Published

1975
1975
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
2
3
2
Order By: Relevance
“…This finding is in disagreement with previous studies [9,10] that no correla tion exists between kidney size and postoperative time. However, those studies assessed renal size only from its length on urograms.…”
Section: Rks-nks (2)contrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in disagreement with previous studies [9,10] that no correla tion exists between kidney size and postoperative time. However, those studies assessed renal size only from its length on urograms.…”
Section: Rks-nks (2)contrasting
confidence: 99%
“…This result is in agreement with Boner et al [9] and Ekelund and Gothlin [1], who found no correlation between renal hypertrophy and patient age. The percent increase in the size of the remaining kid ney was found to be significantly different between the 1 st and 2nd (p < 0.05), and 2nd and 3rd (p < 0.025) year after nephrectomy.…”
Section: Rks-nks (2)supporting
confidence: 92%
“…This is in agreement with the findings of EKELUND & GÖTHLIN (4), w h o have similarly based their results on patients over 40 years of age nephrectomized for renal cancer, a n d also with the study of BONER et al (1). EDGREN et al (3) found the greatest changes in renal size to occur in donors under 40 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…Enlargement has been estimated radiologically by increase in length, in 'index' (product of length times width) or in planimetrically measured length-width area from 1 month to 10 years after nephrec tomy. Length increases by 3.3-9% in most studies [56,139,142,473], index by 18-22% [56,148] and area by about 19% [146]. A few patients in most groups fail to exhibit an increase in kidney length or index [142,148,343,473] and one group of kidney donors showed no average increase in length [217], Studies of children with unilateral atro phic kidney disease illustrate the significant growth-inhi biting effect on their contralateral by small kidneys with little excretory function.…”
Section: Crg In Manmentioning
confidence: 94%